A relação entre os elementos da cocriação, satisfação e confiança no contexto de serviços - Larissa Carine Braz Becker; Cristiane Pizzutti dos Santos; Mateus de Brito Nagel (Brazil, 2022)
New perspectives have emerged in marketing, based, for example, in the co-creation (Vargo & Lusch, 2004). This article aims to analyze the relationship between the elements of co-creation - dialogue, access, risk assessment and transparency -, satisfaction and trust in services with credence qualities (medical services) versus services with experience qualities (hairdresser services). To this end, we conducted a survey (n = 230) and moderated mediation analyses to analysis to investigate satisfaction as a mediator of the relationship between the elements of co-creation and trust, and the moderating role of the type of service. The findings show that satisfaction mediates the relationship between dialogue, access and transparency with trust, and these relationships are stronger for the medical service (credential service) than hairdresser service (experimental service). Thus, this paper contributes to the marketing literature by proposing new antecedents of trust for services with credence qualities, and empirically tests the co-creation through its elements.